Coumarin derivatives inhibit the aggregation of β-lactoglobulin. Issue 27 (8th June 2022) - Parvej, Hasan; Begum, Shahnaz; Dalui, Ramkrishna; Paul, Swarnali; Mondal, Barun; Sardar, Subrata; Sepay, Nayim; Maiti, Gourhari; Halder, Umesh Chandra
Abstract : Aggregation of β-lactoglobulin (β-lg) was inhibited through the stabilization of the native structure by various non-covalent interactions of coumarin derivatives. The 8-hydroxy compound was most effective against the self-assembly of β-lg. Abstract : The binding of a small molecule to a protein through non-covalent interactions mainly depends on its size and electronic environment. Such binding can change the stability of the three dimensional protein structure which sometimes may destabilize it to accelerate or to inhibit protein aggregation. Coumarin is a widely used fluorescent dye with several biological applications. Different substituents (electron-donating and electron-withdrawing) at different positions of the coumarin moiety can influence its molecular volume, physical and chemical properties. Here we investigate the effect of such substituents of coumarin on the aggregation of a model protein, beta-lactoglobulin (β-lg) through a multi spectroscopic approach. It was observed that coumarin methyl ester with an 8-hydroxyl group can inhibit the β-lg aggregation. This compound can bind the hydrophobic site of beta-lactoglobulin and stabilize a particular protein conformation through the formation of hydrogen bond and hydrophobic interactions. Thus a properly designed compound can inhibit protein–protein interactions through protein–small molecule interactions. Other coumarinoid compounds also are effective in the prevention of thermal aggregation of β-lg.